Labor Market and Wage Impacts of HIV/AIDS in Rural Malawi - Dorward, Andrew R.; Mwale, Idrissa (International Food Policy Research Institute, 2006)
There is a limited but growing literature on direct impacts of HIV/AIDS morbidity and mortality on the livelihoods of poor rural people. Less is known, however, about indirect impacts of the HIV/AIDS epidemic on the livelihoods of rural communities, allowing for market interactions between households. These are difficult to study, but unskilled wages and food prices are critically important to the welfare of poor people, whether directly affected by HIV/AIDS or not: If the HIV/AIDS epidemic depresses labor demands more than it contracts labor supply, this could lower wage rates in affected communities, damaging the livelihoods of poor households. Promotion of laborsaving enterprises and technologies under such circumstances could have disastrous consequences for the healthy poor.